Effects of droughts and animal diseases on smallholder farmers’ participation in the South African beef market - Kalaba, Mmatlou W. (University of Pretoria, 2021)
Mini Dissertation (MSc Agric (Agricultural Economics))--University of Pretoria, 2021.